Novel Passivity Analysis for Wind Turbine Systems via Decentralized Event-Triggered Approach - R. Vadivel; T. K. Santhosh; R. Suresh; Nallappan Gunasekaran; Mohammed H. Alsharif; Mun-Kyeom Kim (IEEE Access)
This paper focuses on an innovative passivity analysis of wind turbine systems employing a decentralized event-triggered control approach. To establish new stability conditions, a novel Lyapunov-Krasovskii functional (LKF) is introduced, incorporating information from both the upper and lower bounds of the interval time-varying delay. We provide a new approach to identify the time instants of transmission from the sensors to the controller using just locally available information in event-triggered communication schemes. By using the relaxed integral inequality and the delay decomposition methodology, novel delay-dependent criteria guarantee that the considered system is passive. The passification problem is then handled by designing a decentralized event-triggered controller based on the acquired passivity conditions. The established stability conditions are expressed as linear matrix inequalities (LMIs), which may be numerically verified using the MATLAB LMI toolkit. Finally, a numerical example clearly demonstrates the superiority of our theoretical results using the simulation model.